Effectiveness of six sigma implementation in hard disc manufacturing company - Mohd. Eadey, Eliyana (2013)
In today competitive business world, in order to survive most of the company is continuously improving the quality of their products. Six sigma which is an extension of total quality management (TQM), is used to reduce the process variability and also to provide cost saving to the company. Six sigma has been proven and successfully applied in many companies such as Motorola, General Electric, Allied Signal and etc. Company Aj has been adopting six sigma since September 2009. The objective of this adoption is to reduce the process variation and provide cost saving to the company. Up to 2012, more than 30 projects has been implemented. However the achievement has yet to reach the six sigma level. For further understanding on the problem, a thorough investigation has been carried in this company. The objective for this study is to understand the current implementation of six sigma, identify the critical success factors and obstacles, and propose suggestions for improvement. In order to fulfill this objective, a survey was conducted to determine the critical success factors and obstacles based on respondents perception. Several projects implemented were also reviewed together with Master Black belt and project leader. From the survey, most of the employees agreed that training and development is the most critical success factors. The employees also agreed that insufficient time to conduct the training is most of the obstacle in the six sigma implementation. Although the survey shows training and insufficient times were the critical factors but the most critical factor was management support. Without support from management, the training is unable to be conducted. As a conclusion, management in this organization should give support and commitment toward six sigma in order to make the six sigma implementation to be more successful.